The skin microbiome on healthy and inflammatory altered canine skin determined by next generation sequencing - Štempelová, Lucia; Micenková, Lenka; Andrla, Petr; Strompfová, Viola (Frontiers in Microbiology, 2025)
IntroductionHuman and animal skin is colonized by a complex microbial population. An imbalance of these microorganisms is often associated with dermatological diseases.MethodsThe aim of this work was to describe the skin bacterial microbiota composition of healthy dogs and dogs with inflammatory skin lesions. Genomic DNA was sequenced using primers that target the V4 region of the bacterial 16S rRNA gene. Superficial skin swabs were collected from eight body areas of six healthy dogs (n = 48) and directly from inflammatory altered canine skin (n = 16).ResultsThe skin of healthy dogs was predominantly colonized by phylum Bacillota (34.4 ± 27.2%), followed by Actinomycetota (32.2 ± 20.3%), Pseudomonadota (16.4 ± 12.2%), and Bacteroidota (8.7 ± 11.6%). At the level of genera, Streptococcus spp. (19.4 ± 26.1%) was the most abundant genus across all samples collected from healthy skin, followed by Curtobacterium (5.4 ± 12.1%), Bacteroides (5.2 ± 11.1%) and Corynebacterium_1 (4.3 ± 13.2%). More specifically, Streptococcus spp. was the most abundant on the chin (49.0 ± 35.5%), nose (37.9 ± 32.1%), perianal region (21.1 ± 28.2%), abdomen (11.0 ± 12.8%), dorsal back (12.4 ± 10.3%) and interdigital area (5.5 ± 2.2%). Curtobacterium spp. was predominant on inner pinna (17.8 ± 24.8%) and axilla (6.7 ± 10.8%). Alpha diversity analysis (Shannon index) showed maximum on interdigital area but minimum on a chin (p-value: 0.0416). Beta diversity analysis showed clustering across samples from the individual skin sites but also across samples collected from individual dogs. Staphylococcus spp. was the most abundant genus in 12/16 samples collected from inflammatory skin. In addition, a lower bacterial diversity was observed in samples from skin lesions compared to samples from healthy canine skin.DiscussionThe results confirm the fact that the microbiome of healthy skin is very diverse. Compared to other studies, streptococci predominated on healthy canine skin. Shannon index showed only minor differences in diversity between different parts of canine skin. Results of beta-diversity showed the fact that the main force driving the skin microbiota composition is the individual, followed by the skin site. On the area of skin lesions, dysbiosis was observed with a significant predominance of staphylococci.